2010
DOI: 10.1007/s10741-010-9203-5
|View full text |Cite
|
Sign up to set email alerts
|

When is an optimization not an optimization? Evaluation of clinical implications of information content (signal-to-noise ratio) in optimization of cardiac resynchronization therapy, and how to measure and maximize it

Abstract: Impact of variability in the measured parameter is rarely considered in designing clinical protocols for optimization of atrioventricular (AV) or interventricular (VV) delay of cardiac resynchronization therapy (CRT). In this article, we approach this question quantitatively using mathematical simulation in which the true optimum is known and examine practical implications using some real measurements. We calculated the performance of any optimization process that selects the pacing setting which maximizes an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 16 publications
0
63
0
3
Order By: Relevance
“…Mokrani et al demonstrated a difference in the optimal AV delay at rest and on exercise depending on whether LVOT VTI or maximum LVFT was employed. (10) Using the iterative method, the exact mechanism that the operator is attempting to manipulate, (timing of ventricular filling) is viewed directly, rather than employing a surrogate outcome measure such as LVOT VTI, which is subject to significant variation due to small changes in the angle between the incident ultrasound beam and the outflow tract with respiration, an effect particularly exaggerated during exercise (23,24). As the maximum improvement in cardiac output with AV delay optimization is in the region of 15-20% (1), any technique with a reported reproducibility of 4-10% during optimal resting conditions should be interpreted with caution during exercise, and may underlie the reported mixed results using these methods (5,6,10).…”
Section: Discussionmentioning
confidence: 99%
“…Mokrani et al demonstrated a difference in the optimal AV delay at rest and on exercise depending on whether LVOT VTI or maximum LVFT was employed. (10) Using the iterative method, the exact mechanism that the operator is attempting to manipulate, (timing of ventricular filling) is viewed directly, rather than employing a surrogate outcome measure such as LVOT VTI, which is subject to significant variation due to small changes in the angle between the incident ultrasound beam and the outflow tract with respiration, an effect particularly exaggerated during exercise (23,24). As the maximum improvement in cardiac output with AV delay optimization is in the region of 15-20% (1), any technique with a reported reproducibility of 4-10% during optimal resting conditions should be interpreted with caution during exercise, and may underlie the reported mixed results using these methods (5,6,10).…”
Section: Discussionmentioning
confidence: 99%
“…This permits the relative systolic blood pressure difference between the tested AV delay and reference AV to be determined to high precision. 23,28 The AV delays tested for each patient ranged from 40, 80, 160, 200, 240 ms, and so forth, until intrinsic AV conduction was reached with evidence of LBBB. Parabolic curve fitting was used to improve the precision of determination of the optimum.…”
Section: Av Delay Optimizationmentioning
confidence: 99%
“…Disadvantages of these procedures are that they are time consuming, complicated, expensive, and may even be inaccurate. 1 In a previous study we have shown that optimal LV systolic function can be predicted using mechanical interventricular dyssynchrony (MIVD). 2 In that study, performed in canine LBBB hearts as well as in CRT patients, a MIVD value halfway between its minimal (LV pacing with short AV delay) and maximal value (during LBBB or RV pacing) coincided with optimal systolic function.…”
Section: Clinical Perspective On P 552mentioning
confidence: 99%